An Unusual Case of Laryngeal Paraganglioma in a Patient with Carotid Body Paraganglioma: Multimodality Imaging Findings - Serap Dogan; Serkan Senol; Hakan Imamoglu; Ummuhan Abdulrezzak; Afra Ekinci; Imdat Yuce; Mustafa Ozturk (Case Reports in Radiology)
Multiple paragangliomas of the head and neck are rare conditions. Carotid paragangliomas are most common multiple paragangliomas. Laryngeal paragangliomas are very rare neuroendocrine tumors and usually are seen as symptomatic solitary lesions. We present multimodality imaging findings of incidentally detected laryngeal paraganglioma in a woman with synchronous carotid body paraganglioma and positive family history. To the best of our knowledge, this is the first case of laryngeal and carotid body paragangliomas in a patient with positive family history. Radiologists should keep in mind that paragangliomas may occur in various locations as multiple tumors.